Financial and Economic Analysis of the Robusta Coffee Sector in Tshopo Province - Bopoko Bamenga; Michel Baudouin (Advanced Research in Economics and Business Strategy Journal, 2025)
The aim of the study is to carry out a financial diagnosis, that is to say, to determine the profitability and viability of the robusta coffee sector.